THE IMPACT OF CORPORATE TAX POLICY ON STARTUP ECOSYSTEM IN INDIA (International Journal of Food and Nutritional Sciences, 2023)
India’s startup ecosystem has witnessed exponential growth over the past decade, driven by a confluence of factors such as technological innovation, increased venture capital, and supportive government policies. One of the most significant drivers of this growth is India’s corporate tax policy, which plays a pivotal role in shaping the business environment for startups. This paper explores the impact of India’s corporate tax policy on the startup ecosystem, examining how tax incentives, exemptions, and regulatory frameworks influence the growth, scalability, and sustainability of emerging businesses. The Indian government has introduced several reforms aimed at encouraging entrepreneurship, including tax holidays for newly established startups, exemptions on capital gains, and the introduction of the Startup India scheme in 2016. These initiatives have significantly reduced the financial burden on startups, particularly in the critical early stages of their lifecycle, enabling them to focus on innovation and market expansion. Furthermore, tax incentives have attracted foreign and domestic investments by offering venture capitalists attractive returns with reduced tax liabilities.